Design and Expression of Specific Hybrid Lantibiotics Active Against Pathogenic Clostridium spp. - Cebrián, Rubén; Macia-Valero, Alicia; Jati, Afif P.; Kuipers, Oscar P. (Frontiers in Microbiology, 2019)
C. difficile has been reported as the most common cause of nosocomial diarrhea (antibiotic –associated diarrhea), resulting in significant morbidity and mortality in hospitalized patients. The resistance of the clostridial spores to antibiotics and their side effects on the gut microbiota are two factors related with the emergence of infection and its relapses. Lantibiotics provide an innovative alternative for cell growth inhibition due to their dual mechanism of action (membrane pore forming and cell wall synthesis inhibition) and low resistance rate. Based on the fact that antimicrobials are usually active against bacteria closely related to the producer strains, a new dual approach combining gene mining and synthetic biology was performed, by designing new lantibiotics with high activity and specificity towards Clostridium. We first attempted heterologous expression of putative lantibiotics identified following Clostridium genome mining. Subsequently, we designed new hybrid lantibiotics combining the start or end of the putative clostridial peptides and the start or end parts of nisin. The designed peptides were cloned and expressed using the nisin biosynthetic machinery in Lactococcus lactis. From the 20 initial peptides only 1 fulfilled the requirements established in this work to be considered as a good candidate: high heterologous production level, and high specificity/activity against clostridial species. The high specificity and activity observed for the peptide AMV10 makes it an interesting candidate as an alternative to traditional antibiotics in the treatment of C. difficile infections, avoiding side effects and protecting the normal gut microbiota.